Telerreabilitação de baixo custo por videoconferência em participantes com hipertensão pulmonar: um protocolo de estudo de viabilidade - Silva, Jonathan Luiz da (2023)
Introduction: Current knowledge about telerehabilitation in pulmonary hypertension (PH) is limited. The objective of this study was to investigate the precautions and safety of an alternative low-cost, remote, home-based intervention model. Methods: This is a prediction study in which PH participants were directed to the cardiopulmonary rehabilitation laboratory at Universidade Nove de Julho (UNINOVE). Eligible patients were previously evaluated through clinical field tests and pulmonary function tests (spirometry), functional capacity (6-minute walk test, incremental step test and 1-minute stand-and-sit test), evaluated by measurement of hand grip strength and applicability of the specific quality of life questionnaire (emPHasis-10). Participants were allocated and divided into 2 groups: Control Group (CG), which received a folder with guidelines, health education and incentives to practice physical activity through teleconsultation and telemonitoring twice a week for a period of 2 months and Telerehabilitation Group (ETGLE) that received 16 sessions of aerobic training combined with resistance, twice a week for a period of 2 months lasting 60 minutes. After the intervention protocol, both groups were reevaluated Results: 25 participants with PH were recruited and evaluated, of which 16 were evaluated and included in the initial analyses. Adherence to the telerehabilitation exercise protocol was categorized into three groups and the 96% participation rate at 2 months was considered high adherence. We did not obtain records of adverse events related to telerehabilitation, limiting the safety of the protocol. Furthermore, research participants reported and estimated the costs associated with travel if cardiopulmonary rehabilitation was based on centers per day, twice a week and 16 sessions respectively [(U$90.28)(U$180.57)(U$1444.55)]. ETGLE obtained results in functional capacity after 16 remote training sessions, measured by the total six-minute walking distance (6MWD) in meters (m) and %predict respectively: 6MWD[(525±105m) (88±64%prev)] and by the number of climbs in the pre- and post-intervention incremental step test respectively TDIM [(85±25 climbs) (128±61 climbs)] and improvements observed on the scale (2.5±2). Conclusion: Low-cost telerehabilitation via videoconferencing is feasible and safe in this sample. Furthermore, it was possible to obtain benefits in the post- intervention functional capacity stages with the applicability of this protocol , and observed improvements in quality of life and GrOc.